Has the HIV epidemic peaked? - Bongaarts, J.; Buettner, T.; Heilig, G. K.; Pelletier, F.
gráfs.
pp. 199-224
Keywords: Epidemias; Sida, Sindrome de Inmunodeficiencia Adquirida; Crecimiento Demografico; Africa